Determinants of long acting reversible contraceptive utilisation among women of reproductive age at Balaka district hospital, Malawi - Chank Mwalweni; Ellen Mbweza Chirwa; Eveles Banda Chimala (Elsevier, 2024)
Objectives: Limited studies have examined the factors associated with utilisation of long acting reversible contraceptive (LARC) in Malawi. The purpose of this study was to assess prevalence and determinants of LARC utilisation among women of reproductive age at Balaka district hospital, Malawi. Study design: Facility based cross-sectional study was conducted from 4th July to 28th September 2022. A total of 216 women of reproductive age were selected by a systematic random sampling technique. Data collection was done through face-to-face interviews using a structured and pre-tested questionnaire. Bivariate and multivariate logistic regressions were performed to examine the association between independent variables and utilisation of LARCs. Results were presented as adjusted odds ratios (AOR) with statistical precision at p ≤ 0.05 and 95 % confidence interval (CI). Results: The prevalence of LARC utilisation at the study site was 26.4 %. Couple discussion (AOR = 7.169;95 % CI:1.872-27.453), partner approval (AOR = 11.157; 95 % CI:3.039-40.960), history of unplanned pregnancy (AOR = 3.099; 95 % CI: 1.114-8.622), fear of unplanned pregnancy (AOR = 3.605;95 % CI:1.286-10.107), counselling on LARCs (AOR = 3.829; 95 % CI: 1.070-13.654), number of children (AOR = 1.504; 95 % CI:1.044-2.167) and waiting time at clinic (AOR = 0.315;95 % CI: 0.174-0.571) were identified as the determinants of LARC utilisation. Conclusion: The study found low overall utilisation of LARCs. Strategies to increase LARCs utilisation should consider promoting men's involvement in family planning (FP) activities and address health system related factors including long waiting time at clinic and strengthening counselling on LARC methods.